Proliferation Drives Aging-Related Functional Decline in a Subpopulation of the Hematopoietic Stem Cell Compartment - Kirschner, Kristina; Chandra, Tamir; Kiselev, Vladimir; Flores-Santa Cruz, David; Macaulay, Iain C.; Park, Hyun Jun; Li, Juan; Kent, David G.; Kumar, Rupa; Pask, Dean C.; Hamilton, Tina L.; Hemberg, Martin; et al. (Cell reports (Cambridge), 2017)
Aging of the hematopoietic stem cell (HSC) compartment is characterized by lineage bias and reduced stem cell function, the molecular basis of which is largely unknown. Using single-cell transcriptomics, we identified a distinct subpopulation of old HSCs carrying a p53 signature indicative of stem cell decline alongside pro-proliferative JAK/STAT signaling. To investigate the relationship between JAK/STAT and p53 signaling, we challenged HSCs with a constitutively active form of JAK2 (V617F) and observed an expansion of the p53-positive subpopulation in old mice. Our results reveal cellular heterogeneity in the onset of HSC aging and implicate a role for JAK2V617F-driven proliferation in the p53-mediated functional decline of old HSCs. [Display omitted] •Single-cell transcriptomics reveals functional decline in old HSCs•p53-associated functional decline is driven by prolonged proliferation•Subpopulation of HSCs show aging signature, revealing heterogeneity in the rate of aging Kirschner et al. describe heterogeneous aging of hematopoietic stem cells (HSCs), with a subset of old HSCs displaying signs of functional exhaustion. An increase in proliferation expands the aged HSC subgroup, linking prolonged proliferation to functional decline in HSCs.